Kajian Sosial Ekonomi Perikanan Tangkap Kawasan Pesisir Kabupaten Aceh Timur - jamilah, jamilah; Wardah, Eva; Isnanda Nasution, Wahyu; Budi, Setia; Zuriani, Zuriani; Riani (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
The study aims to examine the socio-economics of capture fisheries in the coastal areas of East Aceh Regency. The socio-economic conditions of capture fisheries are studied using qualitative and quantitative descriptive approaches, including fishermen's activities in fishing, capture fisheries resources, and the economic potential of capture fisheries. Analysis of fishermen's income is carried out to calculate the amount of income and the amount of income distribution among capture fisheries business actors. The results of the study indicate that the potential of fisheries has not been optimally utilized, indicated by the socio-demographic conditions of fishermen who are full of limitations in fishing, difficult access to credit, limited fishing facilities, suboptimal performance of fisheries institutions, no access to capital for fishermen, minimal investment in fish processing, resulting in fish being widely marketed in fresh form. Fishermen's income is still low due to fluctuations in fish catches, limited fishing facilities, and the undeveloped fish processing business. The development of an environmentally conscious aquaculture creative economy, increasing supervision and quality control of fisheries businesses, developing minapolitan fisheries industrialization and marine resources can increase fishermen's income and the welfare of coastal communities in the utilization of marine and fisheries resources.